Sob o fio da navalha : a saúde mental das mulheres a partir da perspectiva de classe social, gênero e raça e/ou etnia - Bolzan, Liana de Menezes (2019)
This thesis aims to analyze how the categories gender, race and/or ethnicity and social class are expressed in the production of knowledge about women's mental health and in public policies on women's health and mental health, in order to contribute to the qualification of interventional strategies for the development of comprehensive care in women's mental health”. For the development of this study, the critical dialectical method was used as an epistemological reference starting from central categories such as totality, historicity and contradiction, being present in the development of the entire work. The investigation is of a qualitative nature and included a theoreticalbibliographical and documental study. The bibliographical research was used with the purpose of knowing the production of knowledge about women's mental health. The theoretical basis of the social class, race and/or ethnicity and gender categories were supported by studies linked to the materialist conception, using the scientific productions of Daniele Kergoat, based on his method of analysis, which understands that the social relations of sex, race and class are conceived in an inseparable way, using the concept of consubstantiality/coextensivity of social relations. The public mental health policies that correspond to the legal apparatus of the Psychiatric Reform, present a generalist approach, without covering the innumerable singularities and social determinants for psychic illness, by assuming this homogeneous and androcentric posture, making women invisible, reinforcing their asymmetries. As well as public health policies for women and mental health, they have fragmented and universalizing characteristics, causing gaps in care processes, since they do not pay attention to the different singularities of users and corroborate the neglect of the right to health and other principles that constitute the SUS. The articulation of gender with the other oppressive categories was scarce in the analyzed studies, by isolating the category, it becomes hierarchical over the others and prevents the complex analysis of the phenomenon, the understanding is thus fragmented and prevents the perception of social structures. However, the productions with the dynamicity of the categories gained prominence in the analyzes presented against the grain on black women, making contributions on this hidden theme in the history of madness and unveiled in this writing. The production of knowledge about women's mental health from the consubstantiality/coextensivity of the categories social class, race and/or ethnicity and gender, demonstrates that these studies are unaware of how social relations are structured and promote exclusion, oppression and inequality to women, as a result, they are determinant for psychic illness and impose themselves as access barriers to mental health care. From the study carried out, it is understood that from the combination of patriarchal, racist and capitalist systems, as structuring in the production of inequalities and social relations, the consubstantiality and coextensivity of the reactions between categories gender, race and/or ethnicity and class corroborate for the production of psychic illness processes in women.